Prevalence of acute adverse reactions among whole blood donors: A 7 years study - Sonam Kumari (Journal of Applied Hematology, 2015)
Background: Donor reaction has the most negative impact on the blood donor return rate. Amelioration of some adverse events has the potential to improve return rate. This study was initiated with the aim to determine the frequency of various adverse reactions. Materials and Methods: The study was conducted over a period of 7 years and 1 month, from July 1, 2007, to August 31, 2014. The donor population analyzed consisted of 27,664 donors (26,557 males and 1107 females). Results: Only 195 donors (0.7%) suffered some adverse reactions. One hundred and fifty-eight (0.57% of the subjects) had mild reactions (agitation, sweating, giddiness, pallor, cold feeling, sense of weakness, nausea), and only 37 (0.13% with 10 females and 27 males) had more severe reactions (including vomiting, fainting, loss of consciousness, and convulsive syncope). Conclusions: Although the number of donors who developed adverse reactions during or immediately after the blood donation was very low, still it is very important to reduce risks to a minimum so that donor return rate could be maintained.